RESEARCH OF DIRECTIONS OF DEVELOPMENT OF LAND MANAGEMENT DOCUMENTATION TAKING INTO ACCOUNT OF MODERN LEGAL REQUIREMENTS - Nesterenko, S.; Radzinska, Y.; Khalikov, S. (Municipal economy of cities. Series: «Economy science», 2022)
Today in Ukraine the issue of defining land as an element in the system of land management, cadastre and evaluation remains relevant. The term "land" means a part of the land that has clearly defined boundaries, a certain location, natural properties, physical parameters, it also describes the legal and economic status. The main properties of the land plot can be considered: boundaries, area, cadastral number and address, as well as legal properties, namely the rights and obligations of the land owner, restrictions and encumbrances, land easements. In addition to these characteristics, there are also so-called quality, they include: the cost of use or exchange. When a land plot is formed, it becomes an object of civil law, and it is for this purpose that it is formed. Nowadays, with the creation of the land market, it is necessary that every owner or user of land has the right to draw up documents necessary for the sale or lease of land, and this includes work on the formation of land, which is also a job. on drawing up according to the project of land management. The purpose of the article is to study the principles and technological aspects of land formation for further creation of land management documentation. The study presents the principles and technological aspects of land formation for their further evaluation in the structure of existing land use and land tenure. The directions of development of technical documentation in the system of land management and cadastre are determined. The mechanism of development of land management projects taking into account modern legal restrictions and market needs is analyzed. It is proved that the necessary condition of land management is to take into account the principles of data collection, processing and preparation of technical documentation. Particular attention is paid to defining modern principles of development of urban planning documentation, based on the latest developments in the industry. The researched issues in the article make a significant contribution to the areas of land management design, formation of cadastral data, development and updating of urban planning documentation and more.